Investment and adaptation as commitment devices in climate policy deteriorate mitigation - Wolfgang Peters; Clemens Heuson; Reimund Schwarze; Anna-Katharina Topp (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The strategy of adaptation to climate change has become a central topic within the UNFCCC negotiations in recent years. On the national level, adaptation plans are elaborated, and on the international level, the need for funding adaptation in developing countries is discussed. This tendency shows that adaptation is likely to be advanced relative to mitigation on the political agenda. Therefore, we analyze the economic consequences of the timing of mitigation and adaptation in a game-theoretic framework regarding as well the importance of technological investments for mitigation. Due to strategic behavior, the activity in mitigation deteriorates when adaptation is advanced. As a consequence, the resulting subgame-perfect equilibrium yields higher total costs. We demonstrate that this result is even reinforced when technological investments are regarded, i.e. the negative effects of advancing adaptation relative to the opposite timing are amplified.
Keywords: Q54; H87; C72; 330